2016
DOI: 10.1097/hjh.0000000000000936
|View full text |Cite
|
Sign up to set email alerts
|

Serum fibroblast growth factor-23 and incident hypertension

Abstract: Elevated serum fibroblast growth factor-23 (FGF23), an endogenous hormone, is associated with disturbed mineral homeostasis, cardiovascular disease, and chronic kidney disease. It is unclear whether FGF23 impacts the development of incident hypertension. We investigated the association of serum FGF23 measured at baseline (1990–92) with incident hypertension at two follow-up visits (1993–95 and 1996–98) in 7,948 middle-aged men and women without hypertension at baseline participating in the Atherosclerosis Risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 47 publications
4
18
0
Order By: Relevance
“…Specific associations have been reported for incident hypertension, LVH, incident HF, higher coronary calcium scores, and incident coronary heart disease 17, 19, 27, 28. In this study we confirmed previous findings reported by Kestenbaum et al linking serum FGF‐23 to incident HF, and further studied the association with subtypes of HFpEF and HFrEF.…”
Section: Discussionsupporting
confidence: 92%
“…Specific associations have been reported for incident hypertension, LVH, incident HF, higher coronary calcium scores, and incident coronary heart disease 17, 19, 27, 28. In this study we confirmed previous findings reported by Kestenbaum et al linking serum FGF‐23 to incident HF, and further studied the association with subtypes of HFpEF and HFrEF.…”
Section: Discussionsupporting
confidence: 92%
“…10 A previous study examining a possible association of FGF23 with incident hypertension in a primarily white population of older adults suggested that individuals in the highest FGF23 decile of values had a modestly increased risk of developing hypertension. 25 Our study extends prior analyses in two significant ways. By the time US adults reach ages 55–64, the prevalence of hypertension already exceeds 50%.…”
Section: Discussionsupporting
confidence: 60%
“…Whether the associations of FGF23 levels with LVH in patients of all ages with [ 6–8 ] or without known CKD [ 46 , 47 ] are mediated through predominantly direct effects of FGF23 on the myocardium independent of hypertension [ 9 ] and renal impairment [ 12 ], or indirectly through BP changes, remains debatable. Most studies reported weak or no independent associations between FGF23 and BP [ 11 ] although recently higher FGF23 levels were independently associated with incident hypertension in younger adults without CKD [ 48 ]. We did not elicit significant associations between FGF23 levels and either systolic or diastolic BP measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these cardiac effects of FGF23 are the result of direct actions targeting the myocardial cells, or indirectly by stimulation of traditional cardiovascular risk factors like hypertension or activation of the renin–angiotensin–aldosterone system (RAAS) remains ill-defined and the subject of ongoing research [ 10 ]. Clinically, the association of hypertension with elevated levels of FGF23 has not been consistent, showing mostly a rather weak association in the absence of overt renal dysfunction [ 11 ], and hypertension may be absent in experimental models where FGF23 levels are elevated [ 12 ]. Of particular interest are the recent experimental data suggesting direct effects of FGF23 on the Na + Cl − co-transporter (NCC) of the renal distal tubular epithelium resulting in Na retention, blood volume expansion, hypertension and cardiac hypertrophy, advancing a novel explanation for the association between higher FGF23 and cardiovascular morbidity and mortality [ 13 ].…”
Section: Introductionmentioning
confidence: 99%